Incidence of Endophthalmitis after Intravitreal Anti-Vascular Endothelial Growth Factor Injections in an Operating Room in China - Yanyun Chen; Wenbin Wei; Demetrios G. Vavvas; Feng Zhang; Haicheng She; Haiying Zhou; Lei Li; Yao Huang; Dimitrios P. Ntentakis; Xiangyu Shi (Journal of Ophthalmology)
Purpose. To evaluate the rate of presumed endophthalmitis (EO) after intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections performed in an operating room (OR) under sterile conditions in mainland China. Methods. Retrospective single-center study between September 2012 and December 2017 at Beijing Tongren Eye Center, Beijing, China. Intravitreal injection database was reviewed. All anti-VEGF injections were performed using a standardized sterile technique in an OR. Injection protocols included antibiotics for 3 days pre-injection, topical 5% povidone-iodine rinsing before the procedure, and post-injection antibiotics for 3 days. Results. A total of 37,830 intravitreal injections were performed at Beijing Tongren Eye Center. Three cases were managed as presumed EO (0.0079%). Positive cultures were documented in 2 of 3 cases. EO incidence following ranibizumab and conbercept administration was 0.0088% (3 in 33,930) and 0% (0 in 3,900), respectively. No significant difference was detected between the two drugs (P=0.745). Conclusions. Very low EO rates were seen in mainland China using a standardized sterile technique in an OR. However, EO could not be completely avoided.